2023
DOI: 10.1136/ard-2023-223929
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal gut microbiome analyses and blooms of pathogenic strains during lupus disease flares

Doua F Azzouz,
Ze Chen,
Peter M Izmirly
et al.

Abstract: ObjectiveWhereas genetic susceptibility for systemic lupus erythematosus (SLE) has been well explored, the triggers for clinical disease flares remain elusive. To investigate relationships between microbiota community resilience and disease activity, we performed the first longitudinal analyses of lupus gut-microbiota communities.MethodsIn an observational study, taxononomic analyses, including multivariate analysis of ß-diversity, assessed time-dependent alterations in faecal communities from patients and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…Overall, these results suggest that both dietary tryptophan and the origin of the microbiota shape the architecture of gut microbiome. This applies specifically to Rg , a group of bacteria now firmly associated with severe lupus 10 , which was found at a greater abundance in recipient microbiota of TC origin and was further enriched by high tryptophan.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Overall, these results suggest that both dietary tryptophan and the origin of the microbiota shape the architecture of gut microbiome. This applies specifically to Rg , a group of bacteria now firmly associated with severe lupus 10 , which was found at a greater abundance in recipient microbiota of TC origin and was further enriched by high tryptophan.…”
Section: Resultsmentioning
confidence: 99%
“…The greater abundance of Rg in the recipients of TC microbiota suggested that these bacteria are enriched in TC mice. Since Rg blooms correspond to disease flares in SLE patients 10 , we speculated that Rg populations may expand with disease progression in TC mice. To test this hypothesis, we longitudinally tested Rg abundance in the feces of age-matched TC and B6 mice housed side by side, in two cohorts each housed in separate rooms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…44,45 In a 4-year study of 16 women with lupus from diverse ethnic backgrounds, five experienced a significant proliferation of the gut bacterium Ruminococcus blautia gnavus concurrent with disease flare-ups. 46 In gastrointestinal diseases, the decrease of butyrate-producing bacteria like Prevotella copri and Roseburia could influence the growth of colon cells and reduced mucus production. 47 Meanwhile, an increase in mucolytic bacteria like Ruminococcus species, virulent Escherichia coli, and Bacteroides fragilis might result in mucosal damage and exacerbated bacterial invasion.…”
Section: Importance Of Gut Microbiota In Health and Diseasementioning
confidence: 99%